2022
DOI: 10.31820/pt.31.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Can Dark Triad Traits in Leaders Be Associated with Positive Outcomes of Transformational Leadership

Abstract: Research that combines dark triad traits and positive leadership styles or outcomes is welcome but still scarce. A quasi-experimental study investigated the mediating role of transformational leadership in linking dark triad leader traits with followers’ extra effort, leadership effectiveness, satisfaction with a leader and the moderating role of culture to these relationships. The moderated mediation model was tested with data from 189 respondents (109 from Lithuania and 80 from Turkey). Participants were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The fact that the leader has a long-standing personality problem may cause this (Goldman, 2006). It is noticeable that the studies that emphasize the dark side of the leader especially use concepts such as narcissism, machiavellianism and psychopathy (Clarke et al, 2015;Lamkin et al, 2017;Stelmokienė and Vadvilavičius, 2022).…”
Section: The Dark Side As a Personality Traitmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the leader has a long-standing personality problem may cause this (Goldman, 2006). It is noticeable that the studies that emphasize the dark side of the leader especially use concepts such as narcissism, machiavellianism and psychopathy (Clarke et al, 2015;Lamkin et al, 2017;Stelmokienė and Vadvilavičius, 2022).…”
Section: The Dark Side As a Personality Traitmentioning
confidence: 99%
“…This type of leadership behavior causes psychological and physical harm to the followers. For this reason, the correct understanding of these dark sides of leaders is extremely important for the well-being of the organization and its employees (Aasland et al, 2010;Stelmokienė and Vadvilavičius, 2022). Detecting, knowing and recognizing negative leader behaviors is an important step in minimizing the psychological and physiological effects on employees.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that Dark Triad traits may not always have uniformly negative effects in leadership roles. According to a study (Stelmokienė, Vadvilavičius, 2022), transformational leadership has been identified as a potential mediator, mitigating the adverse effects of Dark Triad traits and resulting in positive outcomes such as enhanced employee commitment and improved leadership efficacy. Furthermore, narcissistic leaders, characterized by their elevated confidence and charm, have the ability to motivate teams and propel them toward ambitious objectives.…”
Section: Introductionmentioning
confidence: 99%